Qualidade do sono e resiliência de técnicos de radiologia nos serviços hospitalares - Santos, Danusa Passini dos (2023)
Radiology technicians are exposed to physical, emotional and psychological risks due to the characteristics of the hospital work environment. These can interfere with the quality of sleep and cause illness. To this end, resilience has been discussed as a way to minimize the effects of pressure suffered by radiology technicians in their work environment. The objective was to analyze the relationship between sleep quality and the level of resilience in the work of radiology professionals in hospital imaging services. This is a cross-sectional study, carried out in five hospital imaging services in a city in Rio Grande do Sul: Radiology Sector of the Santa Maria University Hospital, Santa Maria General Hospital, Military Brigade Hospital, Santa Maria Regional Hospital and Hospital Casa de Saúde. The inclusion criteria were being a radiology worker and working in the imaging sector. Exclusion criteria: being on leave or leave of any nature during the period of data collection. A sociodemographic characterization instrument was used, the Resilience at Work Scale (RAW Scale Brasil) and the Pittsburgh Sleep Quality Index. Data collection took place from August to November 2022 in person and online. The data were analyzed with a statistical program. Categorical variables were evaluated using absolute (n) and relative frequencies (%), quantitative variables using mean, median, standard deviation, minimum, maximum. Association and correlation tests were carried out and; bivariate analyzes between variables, adopting significance levels of 5%. 37 radiology professionals participated in the study, with a predominance of sex attributed to female birth, average age of 39 years, with children and a partner. These have, on average, 10 years of experience in radiology, work day shifts and have no other job. There was a significant relationship between other employment and working hours (p=0.021). Age proved to be a determining factor in the overall score of resilience at work. Professionals with poor sleep quality and a medium level of resilience at work predominated. The highest resilience score was in the dimension “Finding your calling” and the lowest in the item “Maintaining balance”. A statistically significant correlation was identified between sleep quality and the dimension of resilience in the work “Staying healthy”. There was a statistically significant correlation between sleep quality and the “Staying Healthy” dimension of the Raw Scale Brasil. The evidence obtained can support reflections on the work process in radiology, as well as the importance of resilience and quality of sleep for preventing occupational illness.